2013
DOI: 10.1021/jp308674g
|View full text |Cite
|
Sign up to set email alerts
|

Binding Kinetics and Affinities of Heterodimeric versus Homodimeric HIV-1 Reverse Transcriptase on DNA–DNA Substrates at the Single-Molecule Level

Abstract: During viral replication, HIV-1 reverse transcriptase (RT) plays a pivotal role in converting genomic RNA into proviral DNA. While the biologically relevant form of RT is the p66-p51 heterodimer, two recombinant homodimer forms of RT, p66-p66 and p51-p51, are also catalytically active. Here we investigate the binding of the three RT isoforms to a fluorescently labeled 19/50-nucleotide primer/template DNA duplex by exploiting single-molecule protein-induced fluorescence enhancement (SM-PIFE). PIFE, which does n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 48 publications
3
48
0
Order By: Relevance
“…These related interpretations are consistent with our findings that such shift of the average FRET signal is reduced if the length of the template is significantly smaller or larger than the optimal 20 mer. A plausible third explanation is that the binding of HCV NS5B induces an enhancement of Cy3 emission intensity via protein induced fluorescence enhancement (PIFE), also a distance dependent phenomenon (42)(43)(44). Emission enhancement of Cy3 may give rise in turn to enhanced FRET when Cy5 is in close proximity and may thus account for our observations.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…These related interpretations are consistent with our findings that such shift of the average FRET signal is reduced if the length of the template is significantly smaller or larger than the optimal 20 mer. A plausible third explanation is that the binding of HCV NS5B induces an enhancement of Cy3 emission intensity via protein induced fluorescence enhancement (PIFE), also a distance dependent phenomenon (42)(43)(44). Emission enhancement of Cy3 may give rise in turn to enhanced FRET when Cy5 is in close proximity and may thus account for our observations.…”
Section: Discussionmentioning
confidence: 68%
“…This is in stark contrast with other polymerase enzymes such as HIV-RT, where dissociation events occur within a few seconds under similar conditions (42).…”
Section: Discussionmentioning
confidence: 75%
“…No atomic structures of the p66:p66 immature precursor are available, although several maturation models for HIV-1 RT have been proposed (Jacobo-Molina and Arnold 1991; Davies et al 1991; Tomasselli et al 1993; Zheng et al 2014). In addition, numerous biochemical/biophysical data characterizing the properties of the immature precursor exist (Beard and Wilson 1993; Divita et al 1995; Cabodevilla et al 2001; Braz et al 2010; Marko et al 2013; Sharaf et al 2014; Zheng et al 2015). The p66 immature precursor and mature HIV-1 RT exhibit similar polymerase and RNH activities, but differ in their inter-subunit affinity (Fletcher et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Since PIFE does not require exogenous labeling of RT, it does not require structural perturbation and also may be more accessible to some laboratories than FRET. Furthermore, through observation of signals from T/P in the presence of unlabeled RT, single-molecule protein induced fluorescence enhancement (PIFE) experiments [80] allow the observation of physiologically relevant RT concentrations by providing a workaround to the “concentration problem” [83] seen in single-molecule FRET experiments, which are limited to the use of low nanomolar concentrations of labeled protein. Biophysical studies of RT structure, function and inhibition by NNRTI are all interrelated; e.g., the results from time-resolved single-molecule experiments must be informed by the structural data, the interpretation of which is, in turn, aided by new advances in computational simulation and biophysical techniques to measure protein dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results indicated that modulation of the grip on the T/P substrate itself by NNRTIs may alter RT-T/P dynamics, disfavoring the polymerase mode, suggesting that NNRTI-induced molecular arthritis affects the grip on the template/primer substrate. Intriguingly, it was recently demonstrated that the binding of the various dimeric isoforms of RT could be distinguished using a single-molecule fluorescence method, called Protein-Induced Fluorescence Enhancement (PIFE) [79], where the authors were able to monitor the binding of RT via the fluorescence intensity enhancement of a Cy3-labeled T/P resulting from the proximity of RT to Cy3 [80]. …”
Section: Nnrtis and Their Mechanism Of Actionmentioning
confidence: 99%